GROWTH AND DEVELOPMENT RESPONSE OF GAZANIA (GAZANIA RIGENS) TO DIFFERENT SOURCES OF CROP RESIDUES AS GROWING MEDIA - Abdul Kareem; Aneeq Ahmad; Muhammad Waqas (Science Heritage Journal)
This study investigated effects of various crop residues on Gazania development and growth. A twenty-day pot research was conducted with transplant seedlings on various crop residues as media, including FYM+Silt (1:3), FYM+Silt (1:3) cockscomb and maize residues as treatment Silt as FYM+Silt control (1:3). Completely Randomized Design (RCBD) was applied to test the significance of the treatments and to compare them. The effectiveness data was. FYM+Silt (1:3) was noticeably better at competing with assessed crop residues. As a result, FYM+Silt (1:3) strongly influenced plant height (38.66 cm) with maximum number of leaves (392.00) and more number of branches (45.66) as the control. This result suggests that crop residues affect Gazania’s growth and productivity somewhat positively. In the meantime, FYM+Silt (1:3) are good medium for gazania’s growth performance.